Persian words extraneous in Arabic: القسم الفارسي - ملك م.م. ماجد جاسب (lark, 2019)
Adopted in accomplishing of this research on the extraction of Persian words Arabic research has been divided in to an introduction and four section . in the subject of the first part dealt with conventions along with the names of nature shahs ( trees , flowers and etc ..) . in the second topic dealt conventions name used in industrial stuuf like words, the third topic dealt with religious terminology and in the fourth issue dealt with along with quotes of foregn words and the reason for that citation that you have extracted the Persian words Arabian . I addressed the issue out of every word and the source , who came from the floor depending . on the dictionaries Arabic , Persian and books dealing with these tow languages suite and show felt briefly about revenue and the origin the words and addressed them. Texts of prose , poetry and articles as there are Persian words excreting with extras like apersian or subsequent ( ) suffix other when looking at this conclusion I hope to gain stand more on the core of this topic and identify words that dealt with the nature and the influence of Persian and Arabian languages each other